2005
DOI: 10.1097/01.shk.0000175556.03300.c6
|View full text |Cite
|
Sign up to set email alerts
|

INTERFERON-γ INHIBITION ATTENUATES LETHALITY AFTER CECAL LIGATION AND PUNCTURE IN RATS: IMPLICATION OF HIGH MOBILITY GROUP BOX-1

Abstract: Interferon (IFN)-gamma is an important immunomodulatory agent that is stimulated during infection to aid in host defense. However, increased IFN-gamma levels have been implicated as a mediator in various models of tissue injury and endotoxemia. We have previously shown that inhibition of IFN-gamma decreased bacterial load by accelerating peritoneal fibrin deposition in the cecal ligation and puncture (CLP) model of peritonitis. In addition, circulating inflammatory mediators such as interleukin (IL)-6 were red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
2
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(51 citation statements)
references
References 32 publications
1
47
2
1
Order By: Relevance
“…This deleterious effect was also shown in the CLP model of polymicrobial peritonitis (92) and in a CLP model followed by a P. aeruginosa infection (93). Polymicrobial peritonitis performed in IFN-γ receptor-deficient mice (94) or in rats given anti-IFN-γ antibodies (95) led to the similar demonstration of this negative role. In mice injected with LPS, the ambiguous role of IFN-γ was demonstrated: IFN-γ protected against LPSinduced lung edema but acted in synergy with LPS to enhance the occurrence of death (96).…”
Section: Nk Cells As a Source Of Inflammatory Cytokines And Antimicromentioning
confidence: 65%
“…This deleterious effect was also shown in the CLP model of polymicrobial peritonitis (92) and in a CLP model followed by a P. aeruginosa infection (93). Polymicrobial peritonitis performed in IFN-γ receptor-deficient mice (94) or in rats given anti-IFN-γ antibodies (95) led to the similar demonstration of this negative role. In mice injected with LPS, the ambiguous role of IFN-γ was demonstrated: IFN-γ protected against LPSinduced lung edema but acted in synergy with LPS to enhance the occurrence of death (96).…”
Section: Nk Cells As a Source Of Inflammatory Cytokines And Antimicromentioning
confidence: 65%
“…Consistent with our findings, several studies demonstrated that IFN-γ has harmful effects on hosts with sepsis. Treatment with an anti-IFN-γ antibody significantly decreases mortality in the CLP-induced sepsis model [32], whereas the administration of recombinant IFN-γ significantly enhances it [33]. However, the mechanism by which IFN-γ promotes sepsis has been unclear.…”
Section: Discussionmentioning
confidence: 99%
“…An increasing number of agents (ethyl pyruvate, stearoyl lysophosphatidylcholine, nicotine) dose-dependently inhibits HMGB1 release, and confers significant protection against lethal sepsis [2,8,[35][36][37][38]. Neutralizing antibodies against IFN-γ, a cytokine capable of stimulating HMGB1 release [10], significantly reduced circulating HMGB1 levels in septic rats, and consequently rescued rats from lethal sepsis [39]. Most recently, we discovered that green tea and aqueous extract of a Chinese herb, Angelica sinesis, significantly attenuated endotoxin-induced HMGB1 release [40,41], and rescued mice from lethal sepsis [41].…”
Section: Suppression Of Hmgb1 Release -The Caging Of the Beastmentioning
confidence: 99%